Litter stock in different areas in the process of ecological restoration - Fernandes, Milton Marques; José, Marcelo Brandão; Vieira, Milena Viviane Almeida; Nascimento, Camilla Caroline Fontes; Almeida, André Quintão (Revista de Ciências Agroveterinárias, 2024)
The objective of this study was to quantify and compare the accumulated litter in areas undergoing forest restoration that underwent different management methods. The different types of management methods for restoration were: natural regeneration after clear-cutting of eucalyptus plantations; planting of native species after clear-cutting of eucalyptus plantations; planting of native species after 50% clear-cutting of eucalyptus plantations; and secondary forest (reference). Ten permanent plots of 25 x 25 m were systematically allocated in each area, totaling 40 plots (2.5 ha). Subsequently, the absolute density of tree individuals (ind. ha-1) was measured. Litter (0.25 x 0.25 x 0.05 m) was collected in the center of each plot. Soil density was calculated for each plot at depths of 0-5, 5-10 and 10-20. The normalized difference vegetation index (NDVI) was estimated from spectral images obtained by a remotely piloted aircraft (RPA). Dense 3D point clouds were also generated from digital aerial photogrammetry and canopy openness values ​​were estimated for each plot. Then, the Pearson correlation matrix was calculated between the accumulated litter values ​​and the environmental variables canopy openness, soil density and absolute tree density. The accumulated litter showed a significant positive correlation with NDVI. The different ecological restoration systems, whether intercropped with eucalyptus or only with native forest species, were not efficient in promoting litter accumulation similar to a secondary forest. Eucalyptus did not compete with native forest species and provided a greater amount of accumulated litter. NDVI was the parameter that most correlated with accumulated litter.